2020
DOI: 10.1080/19420676.2020.1758195
|View full text |Cite
|
Sign up to set email alerts
|

Transforming or Complying? The Rise of Social Enterprises in Shanghai

Abstract: A relatively new concept in China, Social Enterprises (SE) have been on the rise in Shanghai. This trend seems to mark a new turn since the so-called 'association revolution', which had brought about an exponential development of NGOs in China over the last three decades. In recent years, a growing number of different actors have emerged, actively promoting a new entrepreneurial approach to social issues and positive community changes. Drawing on ethnographic fieldwork and interviews, the following article ref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 20 publications
(13 reference statements)
0
5
0
Order By: Relevance
“…To meet the above values, six leadership principles have been set, which are: The data collected from the focus group participant's observation, illustrated above, is comparable with the views expressed in other studies in the social enterprise research field. For example, very recent work by Arantes (2020) notes that there has been much conjecture on social enterprise as a result of the impact of the financial crisis of 2008. In her work, Arantes (2020) highlights other studies that have found a similar pattern (see Kim and Defourny, 2011;Poon, 2011).…”
Section: Valuesmentioning
confidence: 99%
See 1 more Smart Citation
“…To meet the above values, six leadership principles have been set, which are: The data collected from the focus group participant's observation, illustrated above, is comparable with the views expressed in other studies in the social enterprise research field. For example, very recent work by Arantes (2020) notes that there has been much conjecture on social enterprise as a result of the impact of the financial crisis of 2008. In her work, Arantes (2020) highlights other studies that have found a similar pattern (see Kim and Defourny, 2011;Poon, 2011).…”
Section: Valuesmentioning
confidence: 99%
“…For example, very recent work by Arantes (2020) notes that there has been much conjecture on social enterprise as a result of the impact of the financial crisis of 2008. In her work, Arantes (2020) highlights other studies that have found a similar pattern (see Kim and Defourny, 2011;Poon, 2011). The increased emergence of social enterprise reflects the realization that social enterprise can have a real, positive impact on society at different levels in many countries across the world.…”
Section: Valuesmentioning
confidence: 99%
“…For some scholars, this association is made through the relationship of enterprise activity to the social, institutional, and environmental factors within a specific context (Kerlin, 2013). Social enterprise has gained increasing currency to fill key gaps caused by the retrenchment of state welfare and to respond to the inclusion or absence of international interest (Arantes, 2020). What this means is social enterprise is a response to certain socioeconomic factors which influence a context's overall civil sector (Kerlin, 2012;Zimmer & Obuch, 2017).…”
Section: Social Enterprise: Context and Purposementioning
confidence: 99%
“…It is the time to be bold and ambitious". In the document have been emphasized not only the need to revive the economy in the short term, but also drawing attention to the necessity of shaping "sustainable future" 7 . "Europe 2020 puts forward three mutually reinforcing priorities:…”
Section: Introductionmentioning
confidence: 99%